2020
DOI: 10.3390/met10060737
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Evolution and Mechanical Properties of Graphene-Reinforced Ti-6Al-4V Composites Synthesized via Spark Plasma Sintering

Abstract: Ti-6Al-4V alloy (TC4) with different concentrations of graphene nanoplatelets (GNPs) were fabricated by ball milling and spark plasma sintering (SPS). Microstructure characteristics of the composites were characterized by X-Ray Diffraction (XRD), Scanning electron microscopy (SEM), and Raman. Microhardness and the compressive mechanical properties were also investigated. Experimental results showed that in the process of SPS, most of the GNPs were still retained at high pressure and temperature, and a new phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Few researchers reinforced graphene into titanium matrix composites (TMCs) using SPS. [30][31][32][33] Wang et al 34 fabricated GNPs reinforced Ti-6Al-4V composites. It was revealed that the strength of the composites depends on the concentration of GNPs.…”
Section: Introductionmentioning
confidence: 99%
“…Few researchers reinforced graphene into titanium matrix composites (TMCs) using SPS. [30][31][32][33] Wang et al 34 fabricated GNPs reinforced Ti-6Al-4V composites. It was revealed that the strength of the composites depends on the concentration of GNPs.…”
Section: Introductionmentioning
confidence: 99%
“…Among these methods, the SPS (Spark Plasma Sintering) method is the most widespread. This technology allows for the obtaining of a wide range of materials [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Graphene-reinforced titanium nanocomposites with different graphene contents have been successfully fabricated by powder metallurgy and rapid consolidation techniques, namely spark plasma sintering (SPS), hot isostatic pressing (HIP), hot pressing (HP), and high-frequency induction heating (HFIH) techniques. Many studies have been focused on the preparation and investigation of the mechanical properties of the consolidated graphene reinforced titanium matrix nanocomposites [ 2 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Thereafter, the machinability analysis of these high-performance materials becomes very necessary after their fabrication and that needs more investigation.…”
Section: Introductionmentioning
confidence: 99%